O-001 A Diagnostic Approach of Immune Dysregulation on Very Early-Onset IBD. (February 2017) - Kelsen, Judith; Dawany, Noor; Conrad, Maire; Sullivan, Kathleen; Behrens, Edward; Devoto, Marcella
Abstract : Background: Immune deficiencies have been associated with inflammatory bowel disease (IBD), and are reported to be particularly enriched in patients with very early-onset IBD (VEO-IBD). However, the actual frequency of primary immune deficiencies in an unselected cohort of patients with VEO-IBD is not known, nor is the optimal screening approach for this population. This study was undertaken to identify a diagnostic approach that will enhance identification of children with primary immune deficiencies who present with VEO-IBD. Methods: Patients who were diagnosed with IBD 5 years of age and younger were recruited. All patients had whole exome sequencing, T and B cell subsets with maturation markers, testing for chronic granulomatous disease, TLR function and NK function performed. Complete metadata analysis was performed including age of onset, phenotype, histology, medication and surgical history and history of unusual infections. Results: One hundred patients with VEO-IBD were included in this study and the majority completed the standardized analysis. At diagnosis, patients with VEO-IBD were more commonly diagnosed with colonic disease than older onset patients ( P < 0.001). Patients with VEO-IBD required surgical intervention more frequently than older-onset IBD ( P < 0.001). A positive family history was seen in 20% of patients. Five patients have had monogenic (XIAP, NLRC4, IL10RA and ZBTB24) immune deficiencies confirmed. Twenty-one patients have tentative gene defects identified but awaiting functional confirmation, including genes involved in the hyperinfammatory pathway (8 patients), immunoregulatory (3), epithelial defects (3) and B cell defects (4) and T cell defects (3). Among these, poor T cell maturation, poor B cell maturation and poor NK function were observed in all but one, suggesting that commonly used flow cytometry approaches may be useful as a filter prior to pursuing WES. All 5 patients with confirmed monogenic or digenic causes had low switched memory B cells. The patient with ZBTB24 deficiency (ICF type 2) had low T cells as did the patient with XIAP deficiency. The patient with STXBP3 deficiency had low T cells and low NK function (K562 and CD107a). Conclusions: A standardized immunology evaluation can provide valuable framework for filtering of patients more likely to have monogenic or digenic causes of VEO IBD. In this cohort, low switched memory B cells and low NK function were the most sensitive for monogenic and digenic causes.